2004
DOI: 10.1111/j.1469-0691.2004.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of sodA sequencing for the identification of clinical isolates of coagulase-negative staphylococci

Abstract: This study evaluated the possible advantages provided by a genotypic method over commercially available biochemical systems for the identification of clinical isolates of coagulase-negative staphylococci (CNS). Partial sequencing of the sodA gene was performed for 168 coagulase-negative clinical isolates of staphylococci identified previously with the ID32 STAPH system. Of these, 101 (60.1%) were identified to the species level with ID32 STAPH, while 67 (39.9%) were misidentified or not identified with certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 14 publications
3
29
0
2
Order By: Relevance
“…The current study revealed that S. haemolyticus and S. epidermidis were the most prevalent CoNS from clinical isolates. This result, in line with many previous studies, confirms the predominance of these two species in various clinical samples compared to other CoNS species (28)(29)(30)(31). In addition, S. haemolyticus and S. epidermidis have been reported to be among the most frequent CoNS species acquiring resistance to multiple antibiotics, which is in agreement with the results of the current study (3,8).…”
Section: Discussionsupporting
confidence: 83%
“…The current study revealed that S. haemolyticus and S. epidermidis were the most prevalent CoNS from clinical isolates. This result, in line with many previous studies, confirms the predominance of these two species in various clinical samples compared to other CoNS species (28)(29)(30)(31). In addition, S. haemolyticus and S. epidermidis have been reported to be among the most frequent CoNS species acquiring resistance to multiple antibiotics, which is in agreement with the results of the current study (3,8).…”
Section: Discussionsupporting
confidence: 83%
“…All isolates were identified to the species level by partial sodA sequencing (23). A disk diffusion method was used for antibiotic susceptibility testing according to the EUCAST 2012 recommendations (http://www.eucast.org/antimicrobial_susceptibility_testing/); strains with inconclusive results for resistance to methicillin were further studied by testing for the mecA gene (24).…”
mentioning
confidence: 99%
“…The "CoNS group" was identified using Gram staining and the following tests: catalase, Slidex latex agglutination (bioMérieux), and tube coagulase (Bio-Rad, Marnes la Coquette, France). CoNS isolates were then identified to the species level by partial sodA sequencing, as described elsewhere (17). The susceptibilities of strains to 15 antibiotics were determined by the disk diffusion method on Mueller-Hinton agar (Bio-Rad) (4) using the following disks: penicillin (6 g), oxacillin (5 g), ofloxacin (5 g), erythromycin (15 g), lincomycin (15 g), pristinamycin (15 g), rifampin (30 g), gentamicin (10 IU), kanamycin (30 g), tobramycin (10 g), tetracycline (30 g), trimethoprim-sulfamethoxazole (1.25 and 23.75 g, respectively), fosfomycin (50 g), vancomycin (30 g), and teicoplanin (30 g).…”
mentioning
confidence: 99%